Conductive polymer dispersion and method for producing the same and capacitor and method for producing the same

A conductive polymer dispersion with controlled viscosity and particle size, comprising a π-conjugated conductive polymer, polyanion, and anionic surfactant, addresses the limitations of conventional dispersions by enabling high-performance solid electrolyte layers in capacitors with reduced ESR.

JP2025008975APending Publication Date: 2025-01-20SHIN ETSU POLYMER CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023111645
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-06
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Conventional conductive polymer dispersions fail to achieve low viscosity and small particle size necessary for penetrating porous dielectric layers, and the resulting solid electrolyte layers do not exhibit high conductivity.

Method used

A conductive polymer dispersion containing a π-conjugated conductive polymer, polyanion, and an anionic surfactant with specific properties is formulated, with controlled viscosity and particle size, allowing for effective penetration and high conductivity.

Benefits of technology

The dispersion facilitates the formation of a high-performance solid electrolyte layer with reduced equivalent series resistance (ESR) in capacitors, enhancing their performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008975000002
    Figure 2025008975000002
  • Figure 2025008975000001
    Figure 2025008975000001
Patent Text Reader

Abstract

To provide a conductive polymer dispersion containing a conductive composite having a moderately low viscosity and a method for producing the same and a capacitor and a method for producing the same.SOLUTION: There is provided a conductive polymer dispersion which contains a conductive composite containing a π-conjugated conductive polymer and a polyanion, an anionic surfactant different from the polyanion and water, wherein the viscosity at 25°C is 10.0 cP or more and 29.0 cP or less. The anionic surfactant is preferably one having a sulfo group and an alkyl group having 6 or more carbon atoms.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive polymer dispersion and a method for producing the same, and a capacitor and a method for producing the same. [Background technology]

[0002] A π-conjugated conductive polymer, the main chain of which is composed of a π-conjugated system, forms a conductive complex by being doped with a polyanion having an anionic group, and becomes dispersible in water. A method for manufacturing a capacitor has been disclosed in which a paint made of a conductive polymer dispersion liquid containing a conductive complex is applied to a dielectric layer provided on the surface of an anode made of a valve metal, the paint is dried to form a solid electrolyte layer, and a cathode is placed opposite the solid electrolyte layer (for example, Patent Document 1). According to this disclosure, the performance of the capacitor is improved by adding a specific unsaturated aliphatic alcohol compound to the paint. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2022-071400 Summary of the Invention [Problem to be solved by the invention]

[0004] Incidentally, the conductive polymer dispersion and the paint containing the conductive polymer dispersion used in the manufacture of the capacitor are required to contain a conductive complex having a moderately low viscosity and preferably a small particle size in order to penetrate into the porous structure of the dielectric layer. In addition, the solid electrolyte layer formed by drying the coating film is required to have high conductivity. Conventional conductive polymer dispersions have not necessarily satisfied these requirements.

[0005] The present invention provides a conductive polymer dispersion containing a conductive complex having an appropriately low viscosity and a method for producing the same, as well as a capacitor and a method for producing the same. [Means for solving the problem]

[0006] [1] A conductive polymer dispersion comprising a conductive complex containing a π-conjugated conductive polymer and a polyanion, an anionic surfactant different from the polyanion, and water, the conductive polymer dispersion having a viscosity of 10.0 cP or more and 29.0 cP or less at 25°C. [2] The conductive polymer dispersion liquid according to [1], wherein the anionic surfactant has a sulfo group and an alkyl group having 6 or more carbon atoms. [3] The conductive polymer dispersion liquid according to [1] or [2], wherein the anionic surfactant comprises one or more selected from the group consisting of hexanesulfonic acid, octanesulfonic acid, dodecylbenzenesulfonic acid, alkylbenzenesulfonic acids having 6 or more carbon atoms, octyl sulfosuccinate, polyoxyalkylsulfuric acids having an alkyl group having 6 or more carbon atoms, and salts thereof. [4] A method for producing a conductive polymer dispersion, comprising: polymerizing the monomer in a reaction liquid containing a polyanion, a monomer of a π-conjugated conductive polymer, an anionic surfactant different from the polyanion, and water, to obtain a conductive polymer dispersion containing a conductive complex containing the π-conjugated conductive polymer and the polyanion, the anionic surfactant, and water, wherein the content of the anionic surfactant relative to the total mass of the reaction liquid is 0.01 mass% or more and 0.400 mass% or less, and the anionic surfactant has a sulfo group and an alkyl group having 6 or more carbon atoms. [5] The method for producing a conductive polymer dispersion liquid according to [4], wherein the anionic surfactant comprises one or more selected from the group consisting of hexanesulfonic acid, octanesulfonic acid, dodecylbenzenesulfonic acid, alkylbenzenesulfonic acids having 6 or more carbon atoms, octyl sulfosuccinate, polyoxyalkylsulfuric acids having an alkyl group having 6 or more carbon atoms, and salts thereof. [6] The method for producing a conductive polymer dispersion liquid according to [4] or [5], wherein the amount of the anionic surfactant in the reaction liquid is 2 to 70 parts by mass per 100 parts by mass of the monomer. [7] The method for producing a conductive polymer dispersion according to any one of [4] to [6], wherein after the polymerization reaction of the monomer, the reaction liquid is brought into contact with an anion exchange resin to obtain the conductive polymer dispersion from which at least a part of the anionic surfactant has been removed. [8] The method for producing a conductive polymer dispersion according to any one of [4] to [7], wherein the conductive polymer dispersion has a viscosity at 25° C. of 10.0 cP or more and 29.0 cP or less. [9] A capacitor comprising an anode made of a porous body of a valve metal, a dielectric layer made of an oxide of the valve metal, a cathode made of a conductive material provided on the side of the dielectric layer opposite the anode, and a solid electrolyte layer formed between the dielectric layer and the cathode, the solid electrolyte layer being made of a cured product of the conductive polymer dispersion according to any one of [1] to [3].

[10] A method for producing a capacitor, comprising the steps of applying the conductive polymer dispersion according to any one of [1] to [3] to a surface of a dielectric layer formed on the surface of an anode made of a porous valve metal, and drying the applied conductive polymer dispersion to form a solid electrolyte layer. Effect of the Invention

[0007] The present invention can provide a conductive polymer dispersion containing a conductive complex having a moderately low viscosity and a method for producing the same, as well as a capacitor and a method for producing the same. The conductive polymer dispersion of the present invention easily permeates into the porous structure of the dielectric layer used in the production of a capacitor, making it possible to produce a high-performance capacitor.

[0008] This invention is believed to contribute to SDGs Goal 12, "Responsible Consumption and Production."

[0009] In this specification and claims, the lower limit and upper limit of a numerical range indicated with "to" are included in the numerical range. [Brief description of the drawings]

[0010] [Figure 1] 1 is a cross-sectional view showing an embodiment of a capacitor of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] ≪Conductive polymer dispersion liquid≫ A first aspect of the present invention is a conductive polymer dispersion liquid comprising a conductive complex containing a π-conjugated conductive polymer and a polyanion, an anionic surfactant different from the polyanion, and water.

[0012] The viscosity of the conductive polymer dispersion of this embodiment at 25° C. is preferably 10.0 cP or more and 29.0 cP or less, more preferably 12.0 cP or more and 28.0 cP or less, and even more preferably 14.0 cP or more and 27.0 cP or less. When the content is equal to or greater than the above lower limit, the composition can be easily applied to and adhered to a substrate such as a dielectric layer, and a thick solid electrolyte layer can be easily formed. When the content is equal to or less than the above upper limit, the fine porous structure of the dielectric layer is easily impregnated, and a high-performance solid electrolyte layer can be easily formed. The viscosity was measured at 25° C. using a tuning fork vibration viscometer in accordance with JIS Z8803:2011 (viscosity measurement method using a vibration viscometer).

[0013] The average particle diameter d (hydrodynamic diameter) of the conductive complex contained in the conductive polymer dispersion of this embodiment is preferably 1000 nm or less, more preferably 800 nm or less, even more preferably 600 nm or less, particularly preferably 500 nm or less, and most preferably 400 nm or less. The lower limit of the average particle diameter d is not particularly limited, and a rough guideline is about 100 nm. The average particle diameter d is determined by adjusting the concentration of the conductive complex contained in the conductive polymer dispersion sample to 1.5 to 1.7 mass %, and measuring the average particle diameter d (hydrodynamic diameter) and polydispersity index by the cumulant method from the autocorrelation function obtained by the photon correlation method using the dynamic light scattering method at 15 to 25° C. For example, the measurement can be performed using a zeta potential / particle size / molecular weight measurement system (ELSZ-2000ZS, manufactured by Otsuka Electronics Co., Ltd.).

[0014] <Conductive composite> The conductive complex of this embodiment includes a π-conjugated conductive polymer and a polyanion. The polyanion in the conductive complex is doped into the π-conjugated conductive polymer to form a conductive complex having electrical conductivity. In the polyanion, only a part of the anionic groups is doped into the π-conjugated conductive polymer, and the polyanion has excess anionic groups that are not involved in the doping. Since the excess anionic groups are hydrophilic groups, the conductive complex has water dispersibility.

[0015] The conductive composite of this embodiment preferably contains a part of the anionic surfactant, and the anionic group contained in the molecule of the anionic surfactant is doped into the π-conjugated conductive polymer, thereby increasing the conductivity of the conductive composite and increasing the water dispersibility of the conductive composite.

[0016] (π-conjugated conductive polymer) The π-conjugated conductive polymer may be an organic polymer whose main chain is composed of a π-conjugated system, and examples thereof include polypyrrole-based conductive polymers, polythiophene-based conductive polymers, polyacetylene-based conductive polymers, polyphenylene-based conductive polymers, polyphenylenevinylene-based conductive polymers, polyaniline-based conductive polymers, polyacene-based conductive polymers, polythiophenevinylene-based conductive polymers, and copolymers thereof. From the viewpoint of stability in air, polypyrrole-based conductive polymers, polythiophenes, and polyaniline-based conductive polymers are preferred, and from the viewpoint of transparency, polythiophene-based conductive polymers are more preferred.

[0017] Polythiophene-based conductive polymers include polythiophene, poly(3-methylthiophene), poly(3-ethylthiophene), poly(3-propylthiophene), poly(3-butylthiophene), poly(3-hexylthiophene), poly(3-heptylthiophene), poly(3-octylthiophene), poly(3-decylthiophene), poly(3-dodecylthiophene), poly(3-octadecylthiophene), poly(3-bromothiophene), poly(3-chlorothiophene), and poly(3-iodothiophene). thiophene), poly(3-cyanothiophene), poly(3-phenylthiophene), poly(3,4-dimethylthiophene), poly(3,4-dibutylthiophene), poly(3-hydroxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxythiophene), poly(3-hexyloxythiophene), poly(3-heptyloxythiophene), poly(3-octyloxythiophene), poly(3-decyloxythiophene), poly(3-dodecyloxythiophene), oxythiophene), poly(3-octadecyloxythiophene), poly(3,4-dihydroxythiophene), poly(3,4-dimethoxythiophene), poly(3,4-diethoxythiophene), poly(3,4-dipropoxythiophene), poly(3,4-dibutoxythiophene), poly(3,4-dihexyloxythiophene), poly(3,4-diheptyloxythiophene), poly(3,4-dioctyloxythiophene), poly(3,4-didecyloxythiophene), poly(3,4-di dodecyloxythiophene), poly(3,4-ethylenedioxythiophene), poly(3,4-propylenedioxythiophene), poly(3,4-butylenedioxythiophene), poly(3-methyl-4-methoxythiophene), poly(3-methyl-4-ethoxythiophene), poly(3-carboxythiophene), poly(3-methyl-4-carboxythiophene), poly(3-methyl-4-carboxyethylthiophene), and poly(3-methyl-4-carboxybutylthiophene). Examples of polypyrrole-based conductive polymers include polypyrrole, poly(N-methylpyrrole), poly(3-methylpyrrole), poly(3-ethylpyrrole), poly(3-n-propylpyrrole), poly(3-butylpyrrole), poly(3-octylpyrrole), poly(3-decylpyrrole), poly(3-dodecylpyrrole), poly(3,4-dimethylpyrrole), poly(3,4-dibutylpyrrole), poly(3-carboxypyrrole), poly(3-methyl-4-carboxypyrrole), poly(3-methyl-4-carboxyethylpyrrole), poly(3-methyl-4-carboxybutylpyrrole), poly(3-hydroxypyrrole), poly(3-methoxypyrrole), poly(3-ethoxypyrrole), poly(3-butoxypyrrole), poly(3-hexyloxypyrrole), and poly(3-methyl-4-hexyloxypyrrole). Examples of polyaniline-based conductive polymers include polyaniline, poly(2-methylaniline), poly(3-isobutylaniline), poly(2-anilinesulfonic acid), and poly(3-anilinesulfonic acid). Among these π-conjugated conductive polymers, poly(3,4-ethylenedioxythiophene) is particularly preferable because of its excellent conductivity, transparency, and heat resistance. The conductive composite may contain one type of π-conjugated conductive polymer, or two or more types of polymers.

[0018] (Polyanion) A polyanion is a polymer having two or more monomer units each having an anionic group in the molecule. The anionic group of the polyanion functions as a dopant for a π-conjugated conductive polymer, improving the conductivity of the π-conjugated conductive polymer. The anion group of the polyanion is preferably a sulfo group or a carboxy group. Specific examples of such polyanions include polymers having a sulfo group, such as polystyrene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyacrylic acid esters having a sulfo group, polymethacrylic acid esters having a sulfo group (for example, poly(4-sulfobutyl methacrylate, polysulfoethyl methacrylate, polymethacryloyloxybenzenesulfonic acid), poly(2-acrylamido-2-methylpropanesulfonic acid), and polyisoprene sulfonic acid; and polymers having a carboxy group, such as polyvinyl carboxylic acid, polystyrene carboxylic acid, polyallyl carboxylic acid, polyacrylic acid, polymethacrylic acid, poly(2-acrylamido-2-methylpropanecarboxylic acid), and polyisoprene carboxylic acid. The polyanion may be a homopolymer in which a single monomer is polymerized, or a copolymer in which two or more monomers are polymerized. Among these polyanions, polymers having a sulfo group are preferred, and polystyrene sulfonic acid is more preferred, since they can provide higher electrical conductivity.

[0019] The weight average molecular weight Mw of the polyanion is not particularly limited and is, for example, preferably from 10,000 to 1,000,000, more preferably from 50,000 to 800,000, and even more preferably from 100,000 to 600,000. When the weight average molecular weight Mw of the polyanion is within the above range, the viscosity of the conductive polymer dispersion of this embodiment becomes appropriately low, and a capacitor with a sufficiently low ESR can be easily produced. The weight average molecular weight Mw of the polyanion is measured by gel filtration chromatography and is the average molecular weight based on mass calculated in terms of pullulan.

[0020] The content ratio of the polyanion contained in the conductive polymer dispersion of this embodiment is, for example, preferably in the range of 1 part by mass to 1000 parts by mass, more preferably 10 parts by mass to 700 parts by mass, and even more preferably 100 parts by mass to 500 parts by mass, relative to 100 parts by mass of the π-conjugated conductive polymer. If the content ratio of the polyanion is equal to or higher than the lower limit, the doping effect on the π-conjugated conductive polymer tends to be stronger, and the conductivity becomes higher. On the other hand, if the content of the polyanion is equal to or lower than the upper limit, the π-conjugated conductive polymer can be sufficiently contained, so that sufficient conductivity can be ensured.

[0021] (anionic surfactant) The anionic surfactant of this embodiment is a low molecular weight having a hydrophilic anionic group and a hydrophobic atomic group in the molecule. The number of anionic groups in the molecule may be one or more than one, but is preferably one from the viewpoint of easily exerting the function as a surfactant. The molecular weight of the anionic surfactant is preferably 100 to 2000, more preferably 200 to 1000. The anionic surfactant is preferably one that can form micelles in water.

[0022] From the viewpoints of reducing the viscosity of the conductive polymer dispersion of this embodiment, easily exerting the effect of reducing the particle size of the conductive composite, and easily doping the π-conjugated conductive polymer, it is preferable that the anionic surfactant has a sulfo group and an alkyl group having 6 or more carbon atoms.

[0023] Specific preferred anionic surfactants include, for example, one or more selected from the group consisting of hexanesulfonic acid, octanesulfonic acid, dodecylbenzenesulfonic acid, alkylbenzenesulfonic acids having 6 or more carbon atoms, octyl sulfosuccinate, and polyoxyalkylsulfuric acids having an alkyl group having 6 or more carbon atoms, and salts thereof. From the viewpoint of fully exerting the function as a surfactant, the number of carbon atoms in the alkyl group of the molecules exemplified here is preferably 6 to 30, more preferably 6 to 20, and even more preferably 6 to 18. The number of carbon atoms may be linear or branched.

[0024] The conductive polymer dispersion liquid of this embodiment may contain one or more kinds of anionic surfactants, and the total content ratio thereof is, for example, preferably 1 to 800 parts by mass, more preferably 10 to 600 parts by mass, and further preferably 100 to 400 parts by mass, relative to 1000 parts by mass of the π-conjugated conductive polymer. If the content is equal to or greater than the lower limit of the range, the interaction with the π-conjugated conductive polymer tends to be stronger, the viscosity of the conductive polymer dispersion is lowered, and the equivalent series resistance (ESR) of the capacitor is further reduced. If the content is equal to or less than the upper limit of the range, the relative content of the π-conjugated conductive polymer is increased, so that sufficient conductivity can be ensured.

[0025] The content of the π-conjugated conductive polymer relative to the total mass of the conductive polymer dispersion of this embodiment is preferably from 0.1 to 1.0 mass%, more preferably from 0.2 to 0.8 mass%, and even more preferably from 0.3 to 0.6 mass%. When the content is within the above suitable range, the conductivity of the conductive layer formed from the conductive polymer dispersion can be increased, and the ESR of a capacitor having a conductive layer (solid electrolyte layer) formed from the conductive polymer dispersion can be further reduced.

[0026] The total content of the π-conjugated conductive polymer and the polyanion relative to the total mass of the conductive polymer dispersion of this embodiment is preferably 0.2 mass% or more and 5.0 mass% or less, more preferably 0.3 mass% or more and 2.5 mass% or less, and even more preferably 0.4 mass% or more and 2.0 mass% or less. When the content is within the above suitable range, the conductivity of the conductive layer formed from the conductive polymer dispersion can be increased, and the ESR of a capacitor having a conductive layer (solid electrolyte layer) formed from the conductive polymer dispersion can be further reduced.

[0027] (dispersion medium) The dispersion medium contained in the conductive polymer dispersion is preferably an aqueous dispersion medium containing water because the conductive complex is hydrophilic. Also, a dispersion medium other than water may be contained. The dispersion medium other than water is not particularly limited as long as it does not significantly impair the dispersibility of the conductive complex. Since the conductive complex has excess anion groups derived from polyanions and has high dispersibility in water, the dispersion medium other than water is preferably a water-soluble organic solvent. Here, the water-soluble organic solvent is an organic solvent that dissolves in an amount of 1 g or more in 100 g of water at 20°C, and examples of the water-soluble organic solvent include alcohol-based solvents, ketone-based solvents, and ester-based solvents. The water-soluble organic solvent contained as the dispersion medium may be one type or two or more types.

[0028] The content of water relative to the total mass of the dispersion medium excluding the solid content (non-volatile components) of the conductive polymer dispersion is preferably 10 mass% or more, more preferably 20 mass% or more, even more preferably 30 mass% or more, and may be 100 mass%. When water is contained in an amount equal to or more than the above lower limit, the dispersibility of the conductive complex contained in the conductive polymer dispersion is increased, the conductivity of the conductive layer formed from the conductive polymer dispersion is increased, and the ESR of a capacitor having a conductive layer (solid electrolyte layer) formed from the conductive polymer dispersion can be further reduced.

[0029] (Polyol Compound) The conductive polymer dispersion may contain one or more polyol compounds. Here, the polyol compound refers to a compound having two or more hydroxyl groups, which is different from the π-conjugated conductive polymer, the polyanion, and the anionic surfactant. By containing a polyol compound, the conductivity of the conductive layer formed from the conductive polymer dispersion can be increased, and the ESR of a capacitor having a conductive layer (solid electrolyte layer) formed from the conductive polymer dispersion can be further reduced.

[0030] Examples of the polyol compound include one or more selected from ethylene glycol, diethylene glycol, propylene glycol, 1,4-butanediol, glycerin, pentaerythritol, trimethylolpropane, and trimethylolethane.

[0031] The content of the polyol compound contained in the conductive polymer dispersion is, for example, preferably 100 parts by mass or more and 10,000 parts by mass or less, more preferably 200 parts by mass or more and 2,000 parts by mass or less, and even more preferably 300 parts by mass or more and 1,000 parts by mass or less, relative to 100 parts by mass in total of the π-conjugated conductive polymer and the polyanion. When the thickness falls within the above preferred range, the conductivity of the conductive layer can be increased, and the ESR of the capacitor can be further reduced.

[0032] The content of the polyol compound relative to the total mass of the conductive polymer dispersion is preferably 0.1 to 10 mass%, more preferably 0.5 to 5.0 mass%, and even more preferably 1.0 to 3.0 mass%. Within the above preferred range, the coatability of the conductive polymer dispersion is improved, the conductivity of the conductive layer is increased, and the ESR of the capacitor can be further reduced.

[0033] (Optional Additives) The conductive polymer dispersion may contain any additive other than the conductive complex within the scope of the present invention, and the content ratio is appropriately determined depending on the type of additive, but can be, for example, 1 to 1000 parts by mass per 100 parts by mass of the total of the π-conjugated conductive polymer and the polyanion. Here, the optional additive is a compound other than the polyol compound and the dispersion medium.

[0034] Examples of the optional additives include a surfactant, an inorganic conductive agent, an antifoaming agent, a coupling agent, an antioxidant, and an ultraviolet absorbing agent. The surfactant may be a nonionic, anionic or cationic surfactant, with the nonionic surfactant being preferred from the standpoint of storage stability. Polymer surfactants such as polyvinyl alcohol and polyvinylpyrrolidone may also be added. Examples of the inorganic conductive agent include metal ions, conductive carbon, etc. Metal ions can be generated by dissolving a metal salt in water. The antifoaming agent includes silicone resin, polydimethylsiloxane, silicone oil, and the like. The coupling agent may be a silane coupling agent having a vinyl group, an amino group, an epoxy group, or the like. Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, and sugars. Examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, salicylate-based ultraviolet absorbers, cyanoacrylate-based ultraviolet absorbers, oxanilide-based ultraviolet absorbers, hindered amine-based ultraviolet absorbers, and benzoate-based ultraviolet absorbers.

[0035] <Method for producing conductive polymer dispersion> A second aspect of the present invention is a method for producing a conductive polymer dispersion, comprising: polymerizing the monomer in a reaction liquid containing a polyanion, a monomer of a π-conjugated conductive polymer, an anionic surfactant different from the polyanion, and water, to obtain a conductive polymer dispersion containing a conductive complex containing the π-conjugated conductive polymer and the polyanion, the anionic surfactant, and water. The conductive polymer dispersion of the first embodiment can be produced by the production method of this embodiment.

[0036] When the monomer is polymerized in the reaction solution to form a π-conjugated conductive polymer, the polyanion is naturally doped into the π-conjugated conductive polymer, and a conductive complex consisting of the π-conjugated conductive polymer and the polyanion is formed. At this time, a part of the anionic groups of the anionic surfactant is doped into the π-conjugated conductive polymer in the same manner as the anionic groups of the polyanion. In this way, the presence of the anionic surfactant in the conductive complex reduces the viscosity of the conductive polymer dispersion liquid produced.

[0037] The synthesis of the conductive complex in the reaction liquid can be carried out in the same manner as in the conventional synthesis of a conductive complex, except that an anionic surfactant is added to the reaction liquid.

[0038] Since the reaction liquid contains water and an anionic surfactant, the polymerization reaction of the monomers proceeds stably, and the resulting conductive complex is obtained in a state where it is stably dispersed in water. The reaction liquid may contain a dispersion medium other than water. The dispersion medium other than water may be any one that does not inhibit polymerization, and is preferably a water-soluble organic solvent. Here, the water-soluble organic solvent is an organic solvent that dissolves in an amount of 1 g or more in 100 g of water at 20°C, and examples of the water-soluble organic solvent include alcohol-based solvents, ketone-based solvents, and ester-based solvents. The water-soluble organic solvent contained as the dispersion medium may be one type or two or more types. The water content relative to the total mass of the dispersion medium (liquid components excluding non-volatile components) of the reaction liquid is preferably 70 mass % or more, more preferably 80 mass % or more, and even more preferably 90 mass % or more, and may be 100 mass %.

[0039] It is preferable to add a known catalyst and oxidizing agent to the reaction solution to promote chemical oxidation of the monomer. Examples of the catalyst include transition metal compounds such as ferric chloride, ferric sulfate, ferric nitrate, and cupric chloride. Examples of the oxidizing agent include persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate.

[0040] The content of the catalyst relative to the total mass of the reaction liquid (including the catalyst) is, for example, preferably from 0.01% by mass to 0.50% by mass, and more preferably from 0.01% by mass to 0.30% by mass.

[0041] The content of the oxidizing agent relative to the total mass of the reaction liquid (including the oxidizing agent) is, for example, preferably from 0.10 mass % to 2.00 mass %, more preferably from 0.30 mass % to 1.50 mass %, and even more preferably from 0.60 mass % to 1.25 mass %.

[0042] The content of the monomer relative to the total mass of the reaction liquid is, for example, preferably from 0.01% by mass to 2.0% by mass, more preferably from 0.1% by mass to 1.0% by mass, and even more preferably from 0.3% by mass to 0.8% by mass. The content of the polyanion relative to the total mass of the reaction solution is, for example, preferably 0.1% by mass to 3.0% by mass, more preferably 0.5% by mass to 2.0% by mass, and even more preferably 1.0% by mass to 1.5% by mass. By setting the content within the above preferred range, a conductive polymer dispersion having the conductive complex concentration in the above preferred content can be easily obtained.

[0043] From the viewpoint of making the content ratio of the π-conjugated conductive polymer and the polyanion in the conductive composite formed by the polymerization reaction to be the above-mentioned suitable ratio, the content ratio of the monomer and the polyanion to be mixed in the reaction solution is preferably in the range of 1 part by mass or more and 1,000 parts by mass or less, more preferably 10 parts by mass or more and 700 parts by mass or less, and even more preferably 100 parts by mass or more and 500 parts by mass or less, relative to 100 parts by mass of the monomer.

[0044] The content of the anionic surfactant relative to the total mass of the reaction liquid is, for example, preferably 0.010 to 0.400 mass%, more preferably 0.030 to 0.350 mass%, further preferably 0.050 to 0.300 mass%, and most preferably 0.07 to 0.270 mass%. When the content is at least the lower limit of the above range, a conductive polymer dispersion having a lower viscosity can be obtained, whereas when the content is no more than the upper limit of the above range, a decrease in the conductivity of the conductive layer formed by curing the obtained conductive polymer dispersion can be suppressed.

[0045] The mass ratio of the amount H1 of the polyanion blended in the reaction solution to the amount H2 of the anionic surfactant blended in the reaction solution, expressed as H1 / H2, is preferably 2.0 to 100.0, more preferably 3.0 to 30.0, and may also be 4.0 to 18.0, or 6.0 to 12.0. When the content is at least the lower limit of the above range, a conductive polymer dispersion having a lower viscosity can be obtained, whereas when the content is no more than the upper limit of the above range, a decrease in the conductivity of the conductive layer formed by curing the obtained conductive polymer dispersion can be suppressed.

[0046] The mass ratio of the amount H3 of the monomer blended in the reaction liquid to the amount H2 of the anionic surfactant blended in the reaction liquid, expressed as H3 / H2, is preferably 1.0 to 50.0, more preferably 1.5 to 20.0, and may also be 2.0 to 8.0, or 2.5 to 5.0. When the content is at least the lower limit of the above range, a conductive polymer dispersion having a lower viscosity can be obtained, whereas when the content is no more than the upper limit of the above range, a decrease in the conductivity of the conductive layer formed by curing the obtained conductive polymer dispersion can be suppressed.

[0047] The reaction temperature in the reaction solution can be, for example, 20 to 30° C. At the reaction temperature, the polymerization reaction is usually completed within about 4 to 12 hours. The end of the polymerization reaction can be confirmed by measurement such as gas chromatography, in which the amount of unreacted monomer in the reaction solution is almost completely consumed.

[0048] It is preferable to remove the catalyst and oxidizing agent added to the reaction solution from the conductive polymer dispersion after the chemical oxidative polymerization of the monomer, and at the same time, it is preferable to remove a part of the anionic surfactant (excess anionic surfactant) contained in the reaction solution. Examples of the removal method include a method of contacting the conductive polymer dispersion with an ion exchange resin and adsorbing the target to be removed to the ion exchange resin, and a method of ultrafiltrating the conductive polymer dispersion to replace the dispersion medium and remove the target. Among these, the method using an ion exchange resin is preferable because it is simple. It is preferable to use a cation exchange resin and an anion exchange resin in combination as the ion exchange resin.

[0049] The conductive polymer dispersion thus obtained contains the desired conductive complex. If the catalyst and oxidizing agent are removed from the reaction solution, the solution can be used as is for the manufacture of a capacitor, which will be described later. Furthermore, the dispersion medium may be replaced with a desired one, the content concentration of the conductive complex may be adjusted, or a polyol compound, any additive, etc. may be added.

[0050] <<Method of manufacturing a capacitor>> A third aspect of the present invention is a method for producing a capacitor, comprising the steps of applying the conductive polymer dispersion of the first aspect to a surface of a dielectric layer formed on the surface of an anode made of a porous valve metal body, and drying the applied conductive polymer dispersion to form a solid electrolyte layer.

[0051] The method for manufacturing a capacitor of this embodiment preferably includes a step of oxidizing the surface of an anode made of a porous valve metal to form a dielectric layer (dielectric forming step), a step of arranging a cathode in a position facing the dielectric layer (cathode forming step), and a step of forming a solid electrolyte layer on at least a part of the surface of the dielectric layer (film forming step). Each step will be described below with reference to FIG.

[0052] [Dielectric formation process] In this step, the surface of anode 11 made of a porous valve metal is oxidized to form dielectric layer 12. The method for forming dielectric layer 12 is not particularly limited, and examples thereof include a method in which the surface of anode 11 is anodized in an electrolyte for chemical conversion treatment, such as an aqueous solution of ammonium adipate, an aqueous solution of ammonium borate, or an aqueous solution of ammonium phosphate.

[0053] [Cathode formation process] In this step, the cathode 13 is disposed at a position facing the dielectric layer 12. The method for disposing the cathode 13 is not particularly limited, and examples thereof include a method of forming the cathode 13 using a conductive paste such as a carbon paste or a silver paste, and a method of disposing a metal foil such as an aluminum foil facing the dielectric layer 12.

[0054] [Film forming process] In this step, the conductive polymer dispersion liquid described above is applied to at least a portion of the surface of the dielectric layer 12, and then dried to form the solid electrolyte layer 14.

[0055] Examples of the conductive polymer dispersion coating method include immersion (dip coating), comma coating, reverse coating, lip coating, and microgravure coating. Of these, a method of immersing the anode 11 in the conductive polymer dispersion under reduced pressure is preferred. The immersion method allows the conductive polymer dispersion to be sufficiently applied even to the inside of the porous structure on the surface of the dielectric layer 12. After immersion, the anode is removed and subjected to the next drying process.

[0056] Examples of the drying method include room temperature drying, hot air drying, far infrared drying, etc. Among these, hot air drying is preferred. The drying temperature is, for example, preferably 100 to 180° C., more preferably 120 to 150° C. The drying time is, for example, preferably 0.2 to 1 hour. After drying, the capacitor can be assembled in the usual manner.

[0057] <Capacitor> A fourth aspect of the present invention is a capacitor comprising an anode made of a porous body of a valve metal, a dielectric layer made of an oxide of the valve metal, a cathode made of a conductive material provided on the side of the dielectric layer opposite the anode, and a solid electrolyte layer formed between the dielectric layer and the cathode, the solid electrolyte layer containing a cured product of the conductive polymer dispersion of the first aspect. The capacitor of the fourth embodiment can be manufactured by the manufacturing method of the third embodiment.

[0058] An example of an embodiment of the fourth aspect will be described with reference to Fig. 1. A capacitor 10 shown in Fig. 1 includes an anode 11 made of a porous body of a valve metal, a dielectric layer 12 made of an oxide of the valve metal, a solid electrolyte layer 14 formed on the surface of the dielectric layer 12, and a cathode 13 provided on the outermost side. The cathode 13 is provided on the opposite side to the anode 11, with the dielectric layer 12 and the solid electrolyte layer 14 sandwiched therebetween.

[0059] Examples of valve metals constituting the anode 11 include aluminum, tantalum, niobium, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony. Among these, aluminum, tantalum, and niobium are preferable. Specific examples of the anode 11 include an aluminum foil that has been etched to increase its surface area and then oxidized, and a tantalum or niobium particle sintered body that has been oxidized and pelletized. Such a processed body is a porous body with irregularities on the surface.

[0060] The dielectric layer 12 in this embodiment is a layer formed by oxidizing the surface of the anode 11, for example, by anodizing the surface of the metallic anode 11 in an electrolyte such as an aqueous solution of ammonium adipate. Similar to the anode 11, the dielectric layer 12 also has projections and recesses.

[0061] The cathode 13 in this embodiment may be a conductive layer formed from a conductive paste or a metal layer made of a conductive material such as aluminum foil.

[0062] The solid electrolyte layer 14 in this embodiment is formed on the surface of the dielectric layer 12. The solid electrolyte layer 14 covers at least a portion of the surface of the dielectric layer 12, and may cover the entire surface of the dielectric layer 12. The thickness of the solid electrolyte layer 14 may be constant or may not be constant, and may be, for example, between 1 μm and 100 μm.

[0063] <Conductive composite> The conductive complex contained in the solid electrolyte layer contains at least a π-conjugated conductive polymer and a polyanion. The polyanion in the conductive complex is doped into the π-conjugated conductive polymer. The conductive complex preferably contains the anionic surfactant.

[0064] The total content of the π-conjugated conductive polymer, polyanion, and anionic surfactant relative to the total mass of the solid electrolyte layer is preferably 1% by mass to 99% by mass, more preferably 50% by mass to 98% by mass, and even more preferably 70% by mass to 97% by mass. The above range is preferable because it makes it easier to reduce the equivalent series resistance of the capacitor.

[0065] <Polyol compound> The solid electrolyte layer may further contain one or more of the above-mentioned polyols. By containing a polyol, the ESR of the capacitor can be further reduced.

[0066] The total content of the polyol compounds contained in the solid electrolyte layer is, for example, preferably 100 parts by mass or more and 10,000 parts by mass or less, more preferably 200 parts by mass or more and 2,000 parts by mass or less, and even more preferably 300 parts by mass or more and 1,000 parts by mass or less, relative to 100 parts by mass in total of the π-conjugated conductive polymer and polyanion contained in the solid electrolyte layer. Within the above preferred range, the ESR of the capacitor can be further reduced.

[0067] [Electrolyte] The capacitor of this embodiment may have an electrolyte that impregnates the solid electrolyte layer. Examples of the solvent constituting the electrolytic solution include alcohol-based solvents such as ethylene glycol, diethylene glycol, propylene glycol, 1,4-butanediol, and glycerin; lactone-based solvents such as γ-butyrolactone, γ-valerolactone, and δ-valerolactone; sulfur-based solvents such as sulfolane, dimethyl sulfoxide, and dimethyl sulfone; amide-based solvents such as N-methylformamide, N,N-dimethylformamide, N-methylacetamide, and N-methylpyrrolidinone; nitrile-based solvents such as acetonitrile and 3-methoxypropionitrile; and water. Examples of the electrolyte constituting the electrolytic solution include organic acids such as adipic acid, glutaric acid, succinic acid, benzoic acid, isophthalic acid, phthalic acid, terephthalic acid, maleic acid, toluic acid, enanthic acid, malonic acid, formic acid, decanedicarboxylic acids such as 1,6-decanedicarboxylic acid and 5,6-decanedicarboxylic acid, octanedicarboxylic acids such as 1,7-octanedicarboxylic acid, azelaic acid, and sebacic acid; or boric acid, a polyhydric alcohol complex compound of boric acid obtained from boric acid and a polyhydric alcohol; inorganic acids such as phosphoric acid, carbonic acid, and silicic acid as anion components, and primary amines (methylamine, ethylamine, propylamine, butylamine, ethylenediamine, etc.), secondary amines (dimethylamine, diethylamine, dipropylamine, methylethylamine, diphenylamine, etc.), tertiary amines (trimethylamine, triethylamine, tripropylamine, triphenylamine, 1,8-diazabicyclo(5,4,0)-undecene-7, etc.), tetraalkylammonium (tetramethylammonium, tetraethylammonium, tetrapropylammonium, tetrabutylammonium, methyltriethylammonium, dimethyldiethylammonium, etc.), etc., as a cationic component.

[0068] The capacitor of this embodiment is not limited to the above configuration, and a separator may be provided between the dielectric layer and the cathode. An example of a capacitor having a separator provided between the dielectric layer and the cathode is a wound capacitor. Examples of the separator include sheets (including nonwoven fabrics) made of cellulose, polyvinyl alcohol, polyester, polyethylene, polystyrene, polypropylene, polyimide, polyamide, polyvinylidene fluoride, etc., and nonwoven fabrics of glass fibers. The density of the separator is, for example, 0.1 g / cm 3 More than 1.0g / cm 3 The following are included: When a separator is provided, a method of forming a cathode by impregnating the separator with carbon paste or silver paste can also be applied. EXAMPLES

[0069] (Production Example 1) Production of polystyrene sulfonic acid; Mw 175,000 110 g of sodium styrenesulfonate was dissolved in 820 ml of ion-exchanged water, and while stirring at 80°C, 4.88 g of sodium peroxodisulfate, which had been dissolved in 55 ml of water in advance, was added dropwise for 2 hours, and the solution was stirred for 4 hours. A cation exchange resin was added to the resulting sodium polystyrenesulfonate-containing solution to remove sodium ions. The solid content of the resulting polystyrenesulfonic acid (PSS) aqueous solution was 10 mass%. The weight-average molecular weight of PSS was measured using a HPLC (high performance liquid chromatography) system with a GPC (gel permeation chromatography) column and pullulan manufactured by Showa Denko K.K. as a standard substance, and the result was 175,000. The measurement by ion chromatography also revealed that the SO4 2- The amount was 3400 ppm.

[0070] [Example 1] (Production of PEDOT-PSS aqueous dispersion) 5.71 g of 3,4-ethylenedioxythiophene, 135.67 g of the aqueous polystyrenesulfonic acid solution obtained in Production Example 1, 0.14 g of dodecylbenzenesulfonic acid (DBSA) as an anionic surfactant, and 782.48 g of ion-exchanged water were mixed at 26°C. The resulting mixed solution was kept at 26°C under a nitrogen atmosphere and stirred while adding an oxidation catalyst solution of 1.15 g of ferric sulfate dissolved in 18.04 g of ion-exchanged water, and then 6.25 g of ammonium persulfate dissolved in 50.56 g of ion-exchanged water was gradually added dropwise over 2 hours, and the mixture was then stirred for another 4 hours to allow the reaction to proceed. The DBSA concentration in the reaction solution was 0.014% by mass. A cation exchange resin and an anion exchange resin were added to the obtained reaction solution to remove the polymerization initiator, iron, and excess anionic surfactant. This resulted in a blue PEDOT-PSS aqueous dispersion with a PEDOT:PSS ratio of 1:2.4 (mass ratio). The solid content (non-volatile components) of the obtained dispersion was adjusted to 1.6 mass% by ultrafiltration.

[0071] (Conductivity evaluation) 1.9 g of the PEDOT-PSS aqueous dispersion obtained above was mixed with 4 g of methanol and 0.1 g of propylene glycol, and the resulting coating material was applied onto a PET film (Lumirror T60, manufactured by Toray Industries, Inc.) using a #12 bar coater and dried at 120°C for 1 minute to obtain a conductive film with a conductive layer formed on the surface. The surface resistance was measured using a resistivity meter (Hiresta, manufactured by Mitsubishi Chemical Analytech Co., Ltd.) at an applied voltage of 10 V. The measurement results are shown in the table. The smaller the surface resistance (unit: Ω / □), the higher the conductivity.

[0072] (viscosity measurement) The PEDOT-PSS aqueous dispersion (1.6% by mass of non-volatile components) obtained above was dispersed using a high-pressure homogenizer, and a portion of it was then taken and measured at 25°C using a tuning fork vibration viscometer (model number: SV-10, manufactured by A&D Co.) in accordance with JIS Z8803:2011 (method of measuring viscosity using a vibration viscometer). The measurement results are shown in the table. In the table, 1 Pa·s (pascal second) is converted to 1000 cP (centipoise).

[0073] [Method of measuring particle size] The PEDOT-PSS aqueous dispersion (non-volatile content 1.6% by mass) obtained above was used as a sample, and the average particle diameter d (hydrodynamic diameter) and polydispersity index were measured by the cumulant method from the autocorrelation function obtained by the photon correlation method using the dynamic light scattering method with a zeta potential, particle size, and molecular weight measurement system (ELSZ-2000ZS, manufactured by Otsuka Electronics Co., Ltd.). The measurement results are shown in the table.

[0074] [Example 2] A PEDOT-PSS aqueous dispersion was obtained in the same manner as in Example 1, except that the amount of DBSA was changed to 0.69 g and the reaction solution was prepared with water so that the total amount (1000 g) did not change, and each measurement was performed. The results are shown in the table. The DBSA concentration in the reaction solution in this example was 0.069 mass%.

[0075] [Example 3] A PEDOT-PSS aqueous dispersion was obtained in the same manner as in Example 1, except that the amount of DBSA was changed to 1.37 g and water was used so that the total amount of the reaction solution did not change, and each measurement was performed. The results are shown in the table. The DBSA concentration in the reaction solution in this example was 0.137% by mass.

[0076] [Example 4] A PEDOT-PSS aqueous dispersion was obtained in the same manner as in Example 1, except that the amount of DBSA was changed to 2.74 g and water was used so that the total amount of the reaction solution did not change, and each measurement was performed. The results are shown in the table. The DBSA concentration in the reaction solution in this example was 0.274 mass%.

[0077] [Example 5] Instead of DBSA, 1.37 g of sodium hexanesulfonate was added, and the reaction solution was prepared with water so that the total amount of the reaction solution did not change. A PEDOT-PSS aqueous dispersion was obtained in the same manner as in Example 1, and each measurement was performed. The results are shown in the table. The concentration of hexanesulfonic acid in the reaction solution in this example was 0.137% by mass.

[0078] [Example 6] Instead of DBSA, 1.37 g of sodium octanesulfonate was added, and the reaction solution was prepared with water so that the total amount of the reaction solution did not change. A PEDOT-PSS aqueous dispersion was obtained in the same manner as in Example 1, and each measurement was performed. The results are shown in the table. The concentration of octanesulfonic acid in the reaction solution in this example was 0.137% by mass.

[0079] [Example 7] Instead of DBSA, 1.37 g of dioctyl sodium sulfosuccinate was added, and the reaction solution was prepared with water so that the total amount of the reaction solution did not change. A PEDOT-PSS aqueous dispersion was obtained in the same manner as in Example 1, and each measurement was performed. The results are shown in the table. The concentration of dioctyl sodium sulfosuccinate in the reaction solution in this example was 0.137 mass%.

[0080] [Example 8] A PEDOT-PSS aqueous dispersion was obtained in the same manner as in Example 1, except that 1.37 g of linear alkylbenzenesulfonate sodium (Newrex Soft 5S, NOF Corp., alkyl chain carbon number 10-16) was added instead of DBSA, and the reaction solution was prepared with water so that the total volume did not change, and each measurement was carried out. The results are shown in the table. The concentration of active components of Newrex Soft 5S in the reaction solution in this example was 0.137 mass%. Note that "Newrex" is a registered trademark.

[0081] [Example 9] Instead of DBSA, 1.37 g of polyoxyethylene alkyl ether sulfate sodium salt (Persoft EF, NOF Corp., alkyl chain carbon number 12 or 14) was added, and the reaction solution was prepared with water so that the total volume did not change. A PEDOT-PSS aqueous dispersion was obtained in the same manner as in Example 1, and each measurement was carried out. The results are shown in the table. The concentration of the effective component of Persoft EF in the reaction solution in this example was 0.137 mass%. Note that "Persoft" is a registered trademark.

[0082] [Comparative Example 1] A PEDOT-PSS aqueous dispersion was obtained in the same manner as in Example 1, except that no anionic surfactant was added and the reaction solution was prepared with water so that the total amount (1000 g) of the reaction solution did not change, and each measurement was performed. The results are shown in the table.

[0083] [Comparative Example 2] A PEDOT-PSS aqueous dispersion was obtained in the same manner as in Example 1, except that the amount of DBSA was changed to 4.11 g and water was added so that the total amount of the reaction solution (1000 g) did not change, and each measurement was performed. The results are shown in the table. The DBSA concentration in the reaction solution in this example was 0.411 mass%.

[0084] [Comparative Example 3] A PEDOT-PSS aqueous dispersion was obtained in the same manner as in Example 1, except that the amount of DBSA was changed to 6.85 g and water was added so that the total amount of the reaction solution (1000 g) did not change, and each measurement was performed. The results are shown in the table. The DBSA concentration in the reaction solution in this example was 0.685% by mass.

[0085] [Comparative Example 4] Instead of DBSA, 1.37 g of propanesulfonic acid was mixed, and the reaction solution was prepared with water so that the total amount of the reaction solution did not change. A PEDOT-PSS aqueous dispersion was obtained in the same manner as in Example 1, and each measurement was performed. The results are shown in the table. The propanesulfonic acid concentration in the reaction solution in this example was 0.137% by mass.

[0086] [Table 1]

[0087] In Examples 1 to 9, a relatively large anionic surfactant having a large number of carbon atoms was contained at a specific concentration, so that the viscosity of the PEDOT-PSS aqueous dispersion was reduced, the diameter of the PEDOT-PSS in the dispersion was reduced, and the conductive layer produced using this had good conductivity. In Comparative Example 1, PEDOT was polymerized without blending an anionic surfactant, and thus an aqueous dispersion of relatively high viscosity containing PEDOT-PSS with a large average particle size was obtained. In Comparative Examples 2 and 3, the amount of the anionic surfactant blended was excessive, so that the conductivity of the conductive layer deteriorated. In Comparative Example 4, since propanesulfonic acid having a relatively small number of carbon atoms was blended, the viscosity of the PEDOT-PSS aqueous dispersion was higher than that of Comparative Example 1. From the above, it was found that the method for producing a conductive polymer dispersion according to the present invention can provide a conductive polymer dispersion having an appropriately low viscosity and containing a conductive complex with a small particle size. It is clear that by using such a conductive polymer dispersion with low viscosity and small particle size, a conductive composite can be easily placed in the small gaps in the electrodes of a capacitor, a solid electrolyte layer with excellent performance can be easily formed, and a capacitor with excellent performance can be obtained. [Explanation of symbols]

[0088] 10 Capacitor 11 Anode 12 Dielectric layer 13 Cathode 14 Solid electrolyte layer

Claims

1. A conductive polymer dispersion liquid comprising a conductive complex containing a π-conjugated conductive polymer and a polyanion, an anionic surfactant different from the polyanion, and water, A conductive polymer dispersion having a viscosity at 25° C. of 10.0 cP or more and 29.0 cP or less.

2. The conductive polymer dispersion liquid according to claim 1 , wherein the anionic surfactant has a sulfo group and an alkyl group having 6 or more carbon atoms.

3. 3. The conductive polymer dispersion liquid according to claim 1, wherein the anionic surfactant comprises at least one selected from the group consisting of hexanesulfonic acid, octanesulfonic acid, dodecylbenzenesulfonic acid, alkylbenzenesulfonic acids having 6 or more carbon atoms, octyl sulfosuccinate, polyoxyalkylsulfuric acids having an alkyl group having 6 or more carbon atoms, and salts thereof.

4. A reaction solution containing a polyanion, a monomer of a π-conjugated conductive polymer, an anionic surfactant different from the polyanion, and water is used to polymerize the monomer, thereby obtaining a polymerizable product. A method for producing a conductive polymer dispersion, which obtains a conductive polymer dispersion containing a conductive complex containing the π-conjugated conductive polymer and the polyanion, the anionic surfactant, and water, comprising the steps of: The content of the anionic surfactant relative to the total mass of the reaction liquid is 0.010% by mass or more and 0.400% by mass or less, The anionic surfactant has a sulfo group and an alkyl group having 6 or more carbon atoms. A method for producing a conductive polymer dispersion.

5. 5. The method for producing a conductive polymer dispersion according to claim 4, wherein the anionic surfactant comprises one or more selected from the group consisting of hexanesulfonic acid, octanesulfonic acid, dodecylbenzenesulfonic acid, alkylbenzenesulfonic acids having 6 or more carbon atoms, octyl sulfosuccinate, polyoxyalkylsulfuric acids having an alkyl group having 6 or more carbon atoms, and salts thereof.

6. The amount of the anionic surfactant in the reaction solution is 2 to 70 parts by mass relative to 100 parts by mass of the monomer; A method for producing the conductive polymer dispersion according to claim 4 or 5.

7. After the polymerization reaction of the monomer, the reaction liquid is brought into contact with an anion exchange resin to obtain the conductive polymer dispersion from which at least a portion of the anionic surfactant has been removed. A method for producing the conductive polymer dispersion according to claim 4 or 5.

8. The method for producing a conductive polymer dispersion according to claim 7 , wherein the conductive polymer dispersion has a viscosity at 25° C. of 10.0 cP or more and 29.0 cP or less.

9. The present invention relates to a valve metal porous body, and a cathode made of a conductive material and provided on the dielectric layer opposite to the anode. A capacitor, wherein the solid electrolyte layer is made of a cured product of the conductive polymer dispersion according to claim 1.

10. 13. A method for producing a capacitor, comprising the steps of: applying the conductive polymer dispersion according to claim 1 to a surface of a dielectric layer formed on a surface of an anode made of a porous valve metal; and drying the conductive polymer dispersion to form a solid electrolyte layer.

Citation Information

Patent Citations

  • Water-dispersible polythiophenes prepared with polymeric acid colloids

    JP2006500463A

  • Method for producing electroconductive polymer fine particle, electroconductive polymer fine particle obtained thereby and aqueous dispersion thereof, and circulation system reaction apparatus used in the production method

    JP2010024304A

  • Conductive polymer suspension, method of manufacturing same, conductive polymer material, electrolytic capacitor, solid electrolytic capacitor, and method of manufacturing same

    JP2010040770A

  • Method for manufacturing capacitor

    JP2010087401A

  • Conductive polymer and conductive composition containing the same, and film having coating film containing the polymer or the composition

    JP2014040549A